Comparing the Trends of Vector-Borne Diseases (VBDs) before and after the COVID-19 Pandemic and Their Spatial Distribution in Southern Iran - Zahra Gheibi; Mitra Boroomand; Aboozar Soltani (Journal of Tropical Medicine)
Objectives. We aimed to model and predict the changes in the trend of vector-borne diseases (VBDs) before and after the COVID-19 pandemic in a high-risk area of Iran. Methods. This case-series study was conducted in Fars province, south of Iran, between April 2016 and July 2021. All referred cases of VBDs were considered during the five years to investigate the effect of the lockdown on the epidemiological profile of these diseases. We used time-series autoregressive integrated moving average (ARIMA) and seasonal ARIMA (SARIMA) models. Results. Pediculosis incidence trend was rising with a peak of 1,146 per 100,000 in 2018, followed by a dramatic decrease reached to the minimum amount of 157.8 per 100,000 in 2021. In contrast, malaria and scabies had a smooth decreasing trend ranging from 2.2 per 100,000 and 7.3 per 100,000 in 2016 to a minimum of 0.2 per 100,000 in 2021, respectively. Likewise, leishmaniasis had a falling trend, with a maximum rate of 82.9 per 100,000 in 2016 to the lowest rate of 9.4 per 100,000 in 2021. However, the difference between observed and expected values revealed that the consequences of the COVID-19 pandemic had increased the number of leishmaniasis cases. Conclusion. Tropical regions of Iran, including Fars province, are the favorite destinations for travelers. During COVID-19 outbreaks, some reasons, such as quarantine, movement restrictions, and social distancing, reduced human-vector contact and finally led to the reduction of VBDs in this area.